RELASI AGAMA, MEDIA DAN MAHASISWA DI UIN TULUNGAGUNG - Wahyudin, Didin (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
This article discusses the relationship between religion, media and students at UIN Tulungagung. In the last decade, the relationship between religion and the media has strengthened. Religion grows and develops in the media as more and more religious figures use the media to convey their preaching messages. At the same time, many young people need religious information and seek it through social media. Using qualitative research methods, this research aims to determine the motivations of young people to follow religious figures on social media, what characteristics of religious figures they like and what implications this has for their understanding. The results show that students follow religious figures to increase their religious insight and as a source of inspiration. Second, students tend to like religious figures who are humorous. The three religious figures have positive implications for students' understanding and religious behavior.